FROSTBITES IN THE PRACTICE OF AN ANESTHESIOLOGIST AND EMERGENCY PHYSICIAN - K. G. Shapovalov (Вестник анестезиологии и реаниматологии, 2019)
Cold injury is a medico-social problem in regions with a sharply continental climate. The article describes approaches to the diagnosis and conservative treatment of frostbite of the extremities. Particular attention is paid to early prediction of the degree of cold damage and intensive therapy methods.